Characterization of Rat Cells Transformed By Hybrid Adenovirus Type 5/12 E1A Genes - Pereira, Sousa Daniel (My University, 1995)
Previously, a series of hybrid adenovirus (Ad) type 5/12 E1A genes were constructed and used in combination with Ad12 E1B to transform primary Hooded Lister rat kidney cells. Research presented here describes the use of the resulting transformed cells lines to identify and characterize functional differences between Ad5 and Ad12 E1A proteins in an attempt to better understand the ability of Ad12 E1-transformed cells, unlike their Ad5 counterparts, to induce tumors in syngeneic immunocompetent rats.
At least two regions within the first exon of Ad12 E1A were identified which mediate tumorigenicity. Expression of either of these regions in the hybrid Ad5/12 E1A-(plus Ad12 E1B) transformed cells was associated with a decrease in cell surface major histcompatibility complex (MHC) class I expression, a finding which suggests that the tumorigenic capacity of Ad12 E1-transformants could be due to their ability to evade lysis by class I-restricted CD8⁺ cytotoxic T lymphocytes (CTLs). However, neither class I down-regulation nor sensitivity to allogeneic CTLs or syngeneic natural killer (NK) cells strictly correlated with the tumorigenic capacities of the hybrids, indicating that additional factors contribute to the differences in the oncogenic potential of rodent cells transformed by the E1 regions of Ad5 and Ad12. Further study demonstrated that at least two regions of Ad5 E1A encode CTL epitopes that confer susceptibility to syngeneic Ad5 El-specific CTLs in vitro while Ad12 E1A expression did not confer susceptibility to syngeneic Ad12 E1-specific CTLs.
The MHC class I enhancer is the target for Ad12 E1A-mediated down-regulation of class I transcription. In Ad12 E1-transformed rodent cells, the class I enhancer is primarily down-regulated through decreased binding of NF-kB (activator) and increased binding of COUP-TF (repressor). Using the hybrid Ad5/12 E1A- (plus Ad12 E1B) transformed rat cells, the same regions of Ad12 E1A implicated in tumorigenesis and down-regulation of class I expression were also found to mediate the differential binding activities of NF-kB and COUP-TF to the class I enhancer in Ad12 E1-transformants. Moreover, it was shown that reduced NF-KB binding activity was not due to decreased expression of its subunits, NF-kB1-p50 (or its precursor, NF-kB1-p105) or RelA-p65 nor to a defect in processing of NF-kB1-p105 to NF-kB1-p50. The latter discovery contradicts a previously published report in which it was suggested that decreased binding NF-kB to the class I enhancer in Ad12 E1-transformed cells was due to impaired processing of NF-kB1-p105 to NF-kB1-p50.
Finally, during studies designed to determine whether the different tumorigenic properties of Ad5 E1- and Ad12 E1-transformed cells were a result of alterations in the composition of their E1A-cellular protein complexes, it was discovered that expression of the Ad12 E1A regions implicated in mediating tumorigenesis, down-regulation of cell surface MHC class I expression, and differential binding of NF-kB and COUP-TF to the class I enhancer also correlated with the presence of a differential phosphorylated form of p300 in Ad12 E1- compared to Ad5 E1-transformed rat cells. This finding suggests that p300 function may be altered in Ad12 E1 - versus Ad5 E1-transformed rodent cells and raises the possibility that p300 may influence tumorigenicity through the regulation of MHC class I expression.
Keywords: Biology; Biology